INNOVATIVE DIRECTIONS IN THE SUSTAINABLE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Rustamov Alisher Rakhmatullaevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article presents ideas and considerations about innovative directions in the sustainable development of small business and private entrepreneurship.